Executive function and learning behaviors: associations with academic skills among preschoolers. Issue 15 (17th November 2020) - Beisly, Amber; Kwon, Kyong-Ah; Jeon, Shinyoung
ABSTRACT: This study examined the associations of preschool children's executive function (EF) and learning behaviour (CLB) with their concurrent academic skills and the role of CLB as a mediator for the EF-academic skills link. One hundred seventy-nine children were assessed on EF and math and literacy skills. Parents and teachers completed a questionnaire that assessed CLB. We found that both EF and CLB were significantly associated with math and literacy skills. However, EF and CLB were not associated, and there was no support for the mediational model of EF on CLB. This finding suggests that EF and CLB may tap unique aspects of children's learning related skills and are directly and independently associated with children's concurrent math and literacy skills.